Introduction of an algorithm for planning of autologous fibular transfer in mandibular reconstruction based on individual bone curvatures. Issue 2 (9th February 2018) - Raith, Stefan; Rauen, Alexandra; Möhlhenrich, Stephan Christian; Ayoub, Nassim; Peters, Florian; Steiner, Timm; Hölzle, Frank; Modabber, Ali
Abstract: Background: Reconstruction of the mandible with autologous transplants is a challenging task and current computer‐aided surgical planning remains cumbersome. Thus, the aim of the present study was to create an automated computational approach for this procedure. Methods: The developed algorithm is based on curves following characteristic anatomical features. Geometrical data from a physiological mandible and a fibula were used to generate six different defects, and geometrical accordance was investigated to demonstrate the applicability of the method with different reconstruction parameters ( n = 309). Results: The method proved to be applicable, it recognized given clinical constraints and the values of accordance could be used to quantify the success of reconstructions. Conclusions: With the present approach, the complex three‐dimensional task of mandibular reconstruction was simplified, and thus it allows implementation in clinical routine. The computational planning that is proposed may be used to design cutting guides or as geometrical input data for real‐time navigated surgery.